The Application of ABC Analysis in the Logistic Warehousing Processes - Kučera, Tomáš; Suk, Antonín (Kaunas University of Technology, 2019)
Each company asks how to reduce costs and waste while maintaining profit growth in a free market environment. Logistics can partly answer this question. Logistics opens the way to a wide range of methods and tools to optimize business. Warehousing and inventory management are one of the company's most important activities in logistics. It is important to ensure that the business is optimally sourced. A number of methods are used for the inventory management and one of them is ABC analysis. ABC analysis is one of the traditional scientific methods used in case studies. If a company has an unnecessary amount of inventory that it is not able to consume, it must spend unnecessary resources to store it. Otherwise, when a company has insufficient inventory, it loses profits from a missed order that can lead to customer losses. ABC analysis is used to inventory management in logistics especially in warehousing. This analysis is one of the methods of differentiated inventory management. The goal of ABC analysis is to divide stock items into three categories according to the classification criteria. ABC analysis is based on the Pareto principle, which means that by controlling 20% of the most important stored items, 80% of the total volume of stored items can be affected. The aim of this article is the application of ABC analysis in a selected company with a view to rationalization of logistic warehousing processes. The article is also based on research of world-renowned literature from the Web of Science database.
Aplikace ABC analýzy v logistických skladovacích procesech
Keywords: ABC analysis, inventory management, logistic warehousing processes; analýza ABC, řízení zásob, logistické skladovací procesy